Structure determination of uracil‐DNA N‐glycosylase from Deinococcus radiodurans in complex with DNA. (1st October 2015) - Pedersen, Hege Lynum; Johnson, Kenneth A.; McVey, Colin E.; Leiros, Ingar; Moe, Elin
<x xml:space="preserve">Abstract</x> Uracil‐DNA N‐glycosylase (UNG) is a DNA‐repair enzyme in the base‐excision repair (BER) pathway which removes uracil from DNA. Here, the crystal structure of UNG from the extremophilic bacterium Deinococcus radiodurans (DrUNG) in complex with DNA is reported at a resolution of 1.35 Å. Prior to the crystallization experiments, the affinity between DrUNG and different DNA oligonucleotides was tested by electrophoretic mobility shift assays (EMSAs). As a result of this analysis, two 16 nt double‐stranded DNAs were chosen for the co‐crystallization experiments, one of which (16 nt AU) resulted in well diffracting crystals. The DNA in the co‐crystal structure contained an abasic site (substrate product) flipped into the active site of the enzyme, with no uracil in the active‐site pocket. Despite the high resolution, it was not possible to fit all of the terminal nucleotides of the DNA complex into electron density owing to disorder caused by a lack of stabilizing interactions. However, the DNA which was in contact with the enzyme, close to the active site, was well ordered and allowed detailed analysis of the enzyme–DNA interaction. The complex revealed that the interaction between DrUNG and DNA is similar to that in the previously determined crystal structure of human UNG (hUNG) in complex with DNA [Slupphaug et al. (1996). Nature (London), 384, 87–92]. Substitutions in a (here defined) variable part of the leucine loop result in a shorter loop (eight residues instead of nine) in DrUNG compared with hUNG; regardless of this, it seems to fulfil its role and generate a stabilizing force with the minor groove upon flipping out of the damaged base into the active site. The structure also provides a rationale for the previously observed high catalytic efficiency of DrUNG caused by high substrate affinity by demonstrating an increased number of long‐range electrostatic interactions between the enzyme and the DNA. Interestingly, specific interactions between residues in the N‐terminus of a symmetry‐related molecule and the complementary DNA strand facing away from the active site were also observed which seem to stabilize the enzyme–DNA complex. However, the significance of this observation remains to be investigated. The results provide new insights into the current knowledge about DNA damage recognition and repair by uracil‐DNA glycosylases.